2019
DOI: 10.1080/03091929.2019.1640875
|View full text |Cite
|
Sign up to set email alerts
|

The onset of thermo-compositional convection in rotating spherical shells

Abstract: Double-diffusive convection driven by both thermal and compositional buoyancy in a rotating spherical shell can exhibit a rather large number of behaviours often distinct from that of the single diffusive system. In order to understand how the differences in thermal and compositional molecular diffusivities determine the dynamics of thermo-compositional convection we investigate numerically the linear onset of convective instability in a double-diffusive setup. We construct an alternative equivalent formulatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…Systematic parameter studies of the linear onset of double-diffusive convection in rotating spherical shells were undertaken by Net et al (2012) and recently by Silva et al (2019). Following Simitev (2011), the study of Silva et al (2019) confirmed that due to distinct "double-diffusive" eigenmodes, critical curves for the onset of thermo-compositional instability are generally multi-valued and form what may be described as "pockets" of instability protruding regions of quiescence. Situations thus arise whereby increasing the thermal or the compositional driving leads to onset of instability at the entry of a pocket and a subsequent return to quiescence as driving is further increased to exit the pocket.…”
Section: Introductionmentioning
confidence: 93%
“…Systematic parameter studies of the linear onset of double-diffusive convection in rotating spherical shells were undertaken by Net et al (2012) and recently by Silva et al (2019). Following Simitev (2011), the study of Silva et al (2019) confirmed that due to distinct "double-diffusive" eigenmodes, critical curves for the onset of thermo-compositional instability are generally multi-valued and form what may be described as "pockets" of instability protruding regions of quiescence. Situations thus arise whereby increasing the thermal or the compositional driving leads to onset of instability at the entry of a pocket and a subsequent return to quiescence as driving is further increased to exit the pocket.…”
Section: Introductionmentioning
confidence: 93%
“…The onset of thermal convection in rapidly rotating spherical shells has been extensively studied, for example, most recently as a special case of the onset of thermo-compositional convection [48]. In general, two major regimes are found at onset-columnar convection and equatorially-attached convection.…”
Section: Linear Onset Of Thermal Convectionmentioning
confidence: 99%
“…To determine accurate values for the critical parameters at onset we use our open source numerical code [50]. The code implements a Galerkin spectral projection method due to Zhang and Busse [51] to solve the linearised versions of Equations (6a) and (6c).…”
Section: Linear Onset Of Thermal Convectionmentioning
confidence: 99%
See 2 more Smart Citations